Mappatemme Aqorang Tradition in Mattampung Ritual Among the Bugis Community in East Kalimantan - Mursalim, Mursalim; Yusran, Yusran; Sagirah, Sitti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The Mappatemme Aqorang tradition in the Mattampung ritual is a tradition of reading the Qur'an 30 juz for the Bugis community in order to pray for the family of the deceased. This research is descriptive-qualitative, meaning that a study was conducted to get a general idea of the mappatemme aqorang tradition. The approach used is a phenomenological approach using the analytical tools of Max Weber's theory of social action. The results showed that the mappatemme aqorang tradition in the mattampung ritual is believed to be a hereditary tradition that has been passed down by its ancestors and as an act of spontaneity carried out for the Bugis community when a family dies by reading the Qur'an, including in the implementation of the mattampung ritual (commemoration of the day of death). In addition, this tradition consciously states that the recitation of the Qur'an has a psychological effect on the family because of the bad anxiety and worry experienced by the family left behind. Finally, this tradition has a value effect in interacting with other communities. The values contained are the values of legiulity (worship), social (friendship, solidarity, and education).